Unveiling metabolo-genomic insights of potent antitumoral and antibiotic activity in Streptomyces sp. VB1 from Valparaíso Bay - Serna-Cardona, Néstor; Zamora-Leiva, Leonardo; Sánchez-Carvajal, Eduardo; Claverías, Fernanda P.; Cumsille, Andrés; Pentón, Karla Alexa; Vivanco, Beatriz; Tietze, Alesia; Tessini, Catherine; Cámara, Beatriz (Frontiers in Microbiology, 2024)
Streptomyces sp. VB1, an actinomycete isolated from marine sediments in Valparaíso Bay, Chile, synthesizes antimicrobial and antiproliferative compounds. This study presents comprehensive metabolomics and comparative genomics analyses of strain VB1. LC-HRMS dereplication and Molecular Networking analysis of crude extracts identified antibiotics such as globomycin and daunorubicin, along with known and potentially novel members of the arylomycin family. These compounds exhibit activity against a range of clinically relevant bacterial and cancer cell lines. Phylogenomic analysis underscores the uniqueness of strain VB1, suggesting it represents a novel taxon. This is further supported by its Biosynthetic Novelty Index (BiNI) and BiG-SCAPE analysis of Gene Cluster Families (GCFs). Notably, two Biosynthetic Gene Clusters (BGCs) were found to be unique to VB1 compared to closely related strains: BGC #15, which encodes potentially novel anthracycline compounds with cancer cell growth inhibition properties, and BGC #28, which features a non-canonical configuration combining arylomycin, globomycin, and siamycin BGCs. This supercluster, the first described to consist of more than two adjacent and functional BGCs, co-produces at least three antimicrobial compounds from different antibiotic families. These findings highlight Streptomyces sp. VB1's potential for discovering new bioactive molecules, positioning it as a promising candidate for further research.